A Model of Surface Residual Stress Distribution of Cold Rolling Spline. (5th September 2017) - Ding, Z. H.; Cui, F. K.; Liu, Y. B.; Li, Y.; Xie, K. G.
Abstract : Residual stress is an important parameter in the evaluation of the performance of a cold rolling spline surface. However, research on cold rolling spline is rare. To improve the surface property of a spline, an involute spline is selected as the object of this study. The contour method for determining cold roll-beating residual stress involves measuring the force spatial distribution, performing a statistical analysis of the experimental results, establishing the parameters for the tooth profile for different positions (dedendum, pitch, and addendum) of residual stress, and determining the effect of pressure on the relationship between stress and the depth of the cold roll-beating. A response surface method is used to establish the spline tooth profile of the dedendum, pitch, and addendum of the residual stress and different depths of the stress layer to obtain the parameters of a multiple regression model and perform a comparative analysis of the experimental and prediction results. Research indicates that the prediction results have high reliability. The establishment of this model has important guiding significance to control the residual stress in the cold roll-beating forming process, optimize the cold roll-beating processing parameters, and improve the surface properties of cold rolling spline.